EVALUASI PENGGUNAAN ANTIHIPERTENSI DI PUSKESMAS BULUSPESANTREN II KEBUMEN MENGGUNAKAN METODE ATC/DDD - Afifah, Zalfa Ifri Nur; Setianingsih, Siti; Kaaffah, Silma (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2025)
Introduction: Hypertension is one of the major health problems and remains the leading cause of cardiovascular morbidity and mortality worldwide. Although many management strategies have been implemented, including the administration of antihypertensive drugs according to indication, most patients still fail to achieve target blood pressure control. This situation highlights the need for evaluating the rational use of antihypertensive drugs in primary healthcare facilities.Objective: This study aimed to evaluate the use of antihypertensive drugs at Buluspesantren II Public Health Center, Kebumen, in 2023 using the Anatomical Therapeutic Chemical/Defined Daily Dose (ATC/DDD) method. Methods: This descriptive study used a retrospective design with data obtained from medical records of patients receiving antihypertensive drugs during January–December 2023. Sampling was conducted using total sampling of all outpatient medical records. Drugs were classified based on the ATC code, and the quantity of drug use was calculated in DDD units and DDD/1000 outpatients per month. Results: The findings showed that the highest use of antihypertensive drugs was amlodipine, amounting to 7768 DDD/1000 outpatients per year, with monthly distribution around 647 DDD/1000 outpatients. Other drugs used included captopril (63 DDD/1000 outpatients), furosemide (20 DDD/1000 outpatients), nifedipine (6 DDD/1000 outpatients), and hydrochlorothiazide (3 DDD/1000 outpatients). Conclusion: Amlodipine was the most widely used antihypertensive drug at Buluspesantren II Public Health Center. Evaluation using the ATC/DDD method provides a quantitative overview of drug utilization, which can serve as a basis for decision-making in achieving more effective and rational antihypertensive therapy management.